“Com você em todo lugar”: Assembleia de Deus e Mídia no Maranhão (1990-2017) - ABREU, Jacimara Sarges (2018)
This dissertation analyzes the relationship between Pentecostalism and media in Maranhão, specifically, its purpose is to study the use of radio Esperança by the Assembly of God on the Island of São Luís (ADISL) and its influence on its institutional growth and, above all, its the number of believers between 1990 and 2017. ADISL, which is a joint or separate entity, is the largest church among the historical and Pentecostal Protestants on the island of São Luís. Radio Esperança was not only the first concession, permission and authorization of radio broadcasting to a church in 1988, as well as in 1990, the year of its beginning, was notable and inaugurated in the radio market in São Luís as the only evangelical station in the state of Maranhão. Currently, in its grid, Radio Esperança relays part of the religious programming of the Southeast region of Brazil: Radio Trans Mundial, São Paulo, and Radio Melodia, Rio de Janeiro; and also has a schedule that unfolds throughout 24 hours, every day, with transmission on the Internet. From these aspects of the broadcaster and considering the diverse academic studies and the shared belief that in modern society the use of the media by the Pentecostal churches has influenced the maintenance and growth of the numbers of the faithful, we have defined as the guiding thread of our work the following question: What is the relationship between Radio Esperança and the growth of ADISL? Like all the research developed, which included data surveys, interviews and the application of questionnaires, and then the detailed analysis of the results obtained, we verified that there is no direct relation between the growth in the number of ADISL faithful and the means of communication, especially with Radio Esperança. In addition to this conclusion, although we hypothesized that the creation of Radio Esperança had as its objective not only to propagate the religious discourse but mainly to grow ADISL, it was verified that the religious practices of the Church developed there, aligned nationally and locally with groups of communication, had no decisive influence on the conversion of the faithful. That is, although ADISL has an instrument like Radio Esperança, a genuine evangelical medium, which makes its range of action broader, the conversions of the faithful happened by other means.